(untitled) (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
English is an important language to learn, because several countries have recognized that English is the language of the world. Therefore, many sources of knowledge come using English. The connection with this journal is that researchers will analyze grade 8 students in learning English, by providing correct and appropriate English learning to students, so that it can be sufficient provision to be brought by students to face the next academic level. This study uses the type of research conducted in the field or field research at SMP Islam Purwadadi. The approach used in this research is a qualitative approach. Researchers used data collection techniques through observation and interviews with English subject teachers, 8th grade students and so on. This study aims to determine the causes of the lack of students’ ability in learning English and provide solutions to overcome students’ learning difficulties at SMP Islam Purwadadi.